Optimalisasi Kesehatan Lansia Jemaat GKPS Tangerang Melalui Kegiatan Latsik.Edu : Optimizing the Health of Elderly Congregants at GKPS Tangerang through Latsik.Edu Activities - Juliani, Enni; Chairunisa, Ratu; Gaol, Elyin A K Lumban (Jurnal Pengabdian Kesehatan, 2025)
Osteoporosis is a major health problem among the elderly, increasing the risk of falls, fractures, disability, and reduced quality of life. Based on bone mineral density screening in elderly members of GKPS Tangerang, 36% were diagnosed with osteoporosis, 47.3% with osteopenia, and only 16.21% were within normal limits. This condition formed the basis for implementing the community service program entitled “Optimization of Elderly Health at GKPS Tangerang Congregation through Latsik.edu (Physical Exercise and Education)”. The program aimed to improve knowledge, skills, and awareness among the elderly in preventing osteoporosis through a combination of health education and structured physical exercise. The methods included a pre-test, interactive counseling on osteoporosis, demonstration of preventive exercises, post-test, and physiotherapy assessment. Exercises consisted of muscle strengthening with therabands, balance training, simple weight-bearing activities, and joint mobilization, supported by physiotherapy modalities such as Infrared (IR), Transcutaneous Electrical Nerve Stimulation (TENS), and Ultrasound Therapy (US). The results showed significant improvement in elderly knowledge, exercise skills, and functional abilities such as standing without assistance and walking more steadily. Participants also reported reduced musculoskeletal pain and joint stiffness. Overall, the Latsik.edu program ran smoothly, received positive responses, and was proven effective as a community-based promotive and preventive effort against osteoporosis.